1979
DOI: 10.1203/00006450-197909000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ketotic Episodes in Glutaryl-CoA Dehydrogenase Deficiency (Glutaric Aciduria)

Abstract: Summawthe ketoacidosis, a pronounced lactic acidosis and lactic aciduria A 7-yr-old boy with glutaryl-CoA dehydrogenase deficiency (glutaric aciduria), presenting periodic episodes of lethargy and ketosis, was studied during two such episodes. The urinary excretions of glutaric and 3-OH-glutaric acids were 3100-7900 and 460-660 &mg creatinine, respectively, during these episodes. Urine samples collected before and after the attacks contained 100-5300 and 230-370 &mg creatinine of glutaric acid and 3-OH-glutari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Urine from hadh ÏȘ/ÏȘ mice had increased excretion of 3-hydroxyglutarate, which has been reported in affected SCHAD-deficient children, and also of glutaconic acid, which is an unstable metabolite derived from glutaconyl-CoA, an intermediate of glutaryl-CoA reduction. This has not been previously detected in affected children but is seen in some patients with glutaryl-CoA dehydrogenase deficiency (17).…”
Section: Resultsmentioning
confidence: 77%
“…Urine from hadh ÏȘ/ÏȘ mice had increased excretion of 3-hydroxyglutarate, which has been reported in affected SCHAD-deficient children, and also of glutaconic acid, which is an unstable metabolite derived from glutaconyl-CoA, an intermediate of glutaryl-CoA reduction. This has not been previously detected in affected children but is seen in some patients with glutaryl-CoA dehydrogenase deficiency (17).…”
Section: Resultsmentioning
confidence: 77%
“…The ability of the straight shortchain monocarboxylic acids and of isovaleric acid to produce coma in experimental animals has been shown (2 1,26), and it has been suggested that the coma seen in isovaleric acidemia and Rey's syndrome may be ascribed to these monocarboxylic acids (26,28). Other features of the acute crises of the organic acidurias are lactic acidosis and, in most cases, ketosis (9,13,18,19,24). These biochemical disturbances may be caused by disturbances of the energy metabolism associated with the citric acid cycle.…”
Section: Speculationmentioning
confidence: 99%
“…We cannot at this point establish whether our data have a pathophysiological significance for glutaric aciduria type I. t GA accumulates in urine for excretion [65, 66], and excretion of this acid may become prominent, exceeding that of 3-hydroxyglutaric acid, during episodes of ketosis [4, 67]. Some studies indicated that the diagnostic relevance of t GA is limited [68], since t GA excretion in urine may be inconsistently found.…”
Section: Discussionmentioning
confidence: 99%